Role of oncogenic KRAS in the prognosis, diagnosis and treatment of colorectal cancer - Gongmin Zhu (BMC, 2021)
Abstract Colorectal cancer (CRC) is a heterogeneous disease at the cellular and molecular levels. Kirsten rat sarcoma (KRAS) is a commonly mutated oncogene in CRC, with mutations in approximately 40% of all CRC cases; its mutations result in constitutive activation of the KRAS protein, which acts as a molecular switch to persistently stimulate downstream signaling pathways, including cell proliferation and survival, thereby leading to tumorigenesis. Patients whose CRC harbors KRAS mutations have a dismal prognosis. Currently, KRAS mutation testing is a routine clinical practice before treating metastatic cases, and the approaches developed to detect KRAS mutations have exhibited favorable sensitivity and accuracy. Due to the presence of KRAS mutations, this group of CRC patients requires more precise therapies. However, KRAS was historically thought to be an undruggable target until the development of KRASG12C allele-specific inhibitors. These promising inhibitors may provide novel strategies to treat KRAS-mutant CRC. Here, we provide an overview of the role of KRAS in the prognosis, diagnosis and treatment of CRC.